If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5w + -1u = w + 4u Reorder the terms: -1u + -5w = w + 4u Reorder the terms: -1u + -5w = 4u + w Solving -1u + -5w = 4u + w Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-4u' to each side of the equation. -1u + -4u + -5w = 4u + -4u + w Combine like terms: -1u + -4u = -5u -5u + -5w = 4u + -4u + w Combine like terms: 4u + -4u = 0 -5u + -5w = 0 + w -5u + -5w = w Add '5w' to each side of the equation. -5u + -5w + 5w = w + 5w Combine like terms: -5w + 5w = 0 -5u + 0 = w + 5w -5u = w + 5w Combine like terms: w + 5w = 6w -5u = 6w Divide each side by '-5'. u = -1.2w Simplifying u = -1.2w
| -105/21=35/n | | p/9=26 | | -2(6y+5z)= | | 7-(x/3)=-2 | | -5(1-5x)+5(-8x-2)=-4x-8r | | B^2-2b+1-49q^2=0 | | 10-x/3=20 | | 9g+2= | | x^3+29x^2+28x=0 | | 12g-5+g(3-4)= | | 168=-8x | | 2x^2+9x=4x+42 | | 1+2nx=3 | | 3x+19=-10 | | 8xy^2+3x^2y=35 | | 0=4x^2-4x-5x^2 | | 10a^2-43a+28=0 | | -5u-w=u+4w | | sqrtx-4=7 | | 10x+2x+13=146 | | 27x+12y+39= | | 7q+14=-55 | | -4(2-y+3y)=3(y-4) | | 10r+11=-2r-1 | | 2x+5(-4x-8)=-184 | | -8p+13=45 | | b+17=-41 | | 14x-13+5x+10+8x+11+10x+5=180 | | 378=-21b | | x-75=-9 | | 2(e-8)+9=5(e+2)-3e-17 | | 378=21b |